(untitled) (Research, Society and Development, 2020)
With the importance that pepper has in the Northeast region of Pará, there was a need to study improvements in the storage of the fruits of the sweet pepper (Capsicum chinense Jacq). Thus, the objective was to evaluate which pre-cleaning time of the fruits, with a solution of hypochlorite dissolved in water, has the best sanitizing action to increase storage durability, as well as to evaluate which packaging, among the chosen ones, has the best response in time to store and better preserve the organoleptic qualities of their fruits. A completely randomized design was used with five replications, a 2x6x2 factorial arrangement, with two cultivars, six immersion times (0 (control), 2, 4, 6, 8 and 10 minutes) in a 2% hypochlorite solution and two packaging forms (trays covered with PVC film and polyethylene bags). The storage took place in an environment with a temperature of 20 ° C ± 2ºC and a relative humidity of 60% ± 5%, for 20 days. The results were standardized and submitted to analysis of variance at 5% and averages test by the Tukey method at 5% probability, using the IBM SPSS Software. It was observed that an immersion of more than 10 minutes ensures better health of the fruits and that trays coated with PVC film offer better condition for the fruits of C. chinense, despite suffering greater weight loss, but better preserving the organoleptic qualities, and there was no significant difference when comparing the two varieties of peppers, however the yellow ones showed less weight loss.